Between Planning and Heritage: Cultural Parks and National Heritage Areas - González, Pablo Alonso; Vázquez, Alfredo Macías (European Spatial Research and Policy, 2015)
The number of cultural parks and heritage areas is increasing in Europe and the United States. Those are spreading over other areas where the economic sectors related to tourism and leisure gain weight. Heritage areas or parks are heterogeneous initiatives that place cultural heritage at the heart of spatial planning policy and economic development, aiming at the reinvention of large territories and local community participation in planning. Their relevance stems from their potential influence on the territorial configuration of broad regions and their impact upon the articulation of traditional protected areas. Notwithstanding this, they have attracted scant academic attention so far.